Induction of Deoxyribonucleic Acid Synthesis in Potato Tuber Slices: Role of Protein Synthesis - Watanabe, Akira (1976)
Timing of protein synthesis which is a prerequisite to DNA synthesis induced in potato tuber tissue (Solanum tuberosum L.) by cut injury has been studied using cycloheximide. The induction of DNA synthesis which was measured by incorporation of (3)H-thymidine was completely inhibited when the inhibitor was applied to the tuber discs immediately after slicing. When the application of cycloheximide was delayed for 6 hours or more after slicing, DNA synthesis was observed but its rate was reduced to 20% of control. The inhibitory effect of cycloheximide, however, rapidly decreased when the inhibitor was applied at 6 or less hours immediately prior to determination of DNA synthesis. The effect of cycloheximide on the incorporation of (14)C-leucine suggests that the change in the effect of cycloheximide on the induction of DNA synthesis is not due to incomplete inhibition of protein synthesis. Cycloheximide did not have significant effects on either uptake or phosphorylation of (3)H-thymidine in the discs. Inhibition of both protein and DNA synthesis by cycloheximide was reversed by washing and further incubation of the discs. Almost no qualitative difference was detected by buoyant density analysis between DNA formed under inhibition of protein synthesis of the later stage and DNA synthesized under normal conditions. These results suggest that DNA synthesis induced in potato tuber tissue by cut injury requires continuous synthesis of new protein molecules in a characteristically programmed sequence.